The Influence of Green Promotion and Environmental Awareness on the Perceived Value of Low Watt Rice Cooker through Eco-Friendly Attitude in Generation Z in Surabaya - Agus Sastriono; Siti Mujanah; Abdul Halik Abdul Halik (Journal of Industrial Engineering & Management Research, 2026)
This study aims to analyze the influence of green promotion and environmental awareness on the perceived value of low-watt rice cookers through eco-friendly attitude among Generation Z in Surabaya City. The novelty of this research lies in the use of eco-friendly attitude as a mediating variable in the relationship between green promotion and environmental awareness toward perceived value in energy-efficient electronic products, particularly low-watt rice cookers. This study employed a quantitative approach with data collected through questionnaires distributed to Generation Z consumers in Surabaya City who are familiar with low-watt rice cooker products. The sampling technique used was purposive sampling, while the data analysis method applied was Partial Least Square-Structural Equation Modeling (PLS-SEM) using SmartPLS software. The results indicate that green promotion and environmental awareness have a positive and significant effect on eco-friendly attitude and the perceived value of low-watt rice cookers. Furthermore, eco-friendly attitude also has a positive and significant effect on perceived value and is proven to mediate the influence of green promotion and environmental awareness on the perceived value of low-watt rice cookers among Generation Z in Surabaya City.